The Chemokine Receptor CXCR3 Isoform B Drives Breast Cancer Stem Cells - Namita Kundu; Xinrong Ma; Regine Brox; Xiaoxuan Fan; Tyler Kochel; Jocelyn Reader; Nuska Tschammer; Amy Fulton (Breast Cancer: Basic and Clinical Research, 2019)
We are seeking to identify molecular targets that are relevant to breast cancer cells with stem-like properties. There is growing evidence that cancer stem cells (CSCs) are supported by inflammatory mediators expressed in the tumor microenvironment. The chemokine receptor CXCR3 binds the interferon-γ-inducible, ELR-negative CXC chemokines CXCL9, CXCL10, and CXCL11 and malignant cells have co-opted this receptor to promote tumor cell migration and invasion. There are 2 major isoforms of CXCR3: CXCR3A and CXCR3B. The latter is generated from alternative splicing and results in a protein with a longer N-terminal domain. CXCR3 isoform A is generally considered to play a major role in tumor metastasis. When the entire tumor cell population is examined, CXCR3 isoform B is usually detected at much lower levels than CXCR3A and for this, and other reasons, was not considered to drive tumor progression. We have shown that CXCR3B is significantly upregulated in the subpopulation of breast CSCs in comparison with the bulk tumor cell population in 3 independent breast cancer cell lines (MDA-MB-231, SUM159, and T47D). Modulation of CXCR3B levels by knock in strategies increases CSC populations identified by aldehyde dehydrogenase activity or CD44 + CD24 − phenotype as well as tumorsphere-forming capacity. The reverse is seen when CXCR3B is gene-silenced. CXCL11 and CXCL10 directly induce CSC. We also report that novel CXCR3 allosteric modulators BD064 and BD103 prevent the induction of CSCs. BD103 inhibited experimental metastasis. This protective effect is associated with the reversal of CXCR3 ligand-mediated activation of STAT3, ERK1/2, CREB, and NOTCH1 pathways. We propose that CXCR3B, expressed on CSC, should be explored further as a novel therapeutic target.